Analysis of Hydrogen Gas Production Results in Water Electrolysis Process on Genset Characteristics - Djoko Hari Praswanto; Soeparno Djiwo; Bima R. P. D Palevi (Widyagama University of Malang, 2023)
Hydrogen gas is a type of alternative fuel for transportation that can serve a number of other potential needs. Water electrolysis is one way to get hydrogen gas. This study aims to determine the results of water electrolysis with three catalysts and mixed metal electrodes which are then applied to generator motor engines. The research method used was an experimental method with variations in electrolysis using KOH and NaOH base catalysts, H2SO4 acid catalysts, and stainless steel 316 electrodes. The best results for H2 gas production in this study were obtained with a 2M H2SO4 catalyst with a gas yield of 244.9mL H2 gas, while The lowest yield in this study was the 1M concentration of 1M NaOH catalyst of 12.5mL. The best results for H2 gas production were varied with pertalite fuel and then tested with a generator engine. Testing the generator motor engine is measured arm length and mass with a machine dynamometer. After testing, the data is obtained which is then analyzed to obtain the value of torque (Nm) and electric motor power (kW), and driving motor power (HP). The maximum energy produced pertalite + H2 gas has increased by 2.27kW on the electric motor and power of 4.13HP on the driving motor, while for pertalite fuel alone the power generated is 1.44kW on the electric motor and power of 2.62HP on the driving motor.[1] S. A. Grigoriev, V. N. Fateev, D. G. Bessarabov, and P. Millet, “Current status, research trends, and challenges in water electrolysis science and technology,” Int. J. Hydrogen Energy, vol. 45, no. 49, pp. 26036–26058, 2020, doi: 10.1016/j.ijhydene.2020.03.109.[2] Y. Song, X. Zhang, K. Xie, G. Wang, and X. Bao, “High-Temperature CO2 Electrolysis in Solid Oxide Electrolysis Cells: Developments, Challenges, and Prospects,” Adv. Mater., vol. 31, no. 50, pp. 1–18, 2019, doi: 10.1002/adma.201902033.[3] A. Nechache and S. Hody, “Alternative and innovative solid oxide electrolysis cell materials: A short review,” Renew. Sustain. Energy Rev., vol. 149, 2021, doi: 10.1016/j.rser.2021.111322.[4] O. Schmidt, A. Gambhir, I. Staffell, A. Hawkes, J. Nelson, and S. Few, “Future cost and performance of water electrolysis: An expert elicitation study,” Int. J. Hydrogen Energy, vol. 42, no. 52, pp. 30470–30492, 2017, doi: 10.1016/j.ijhydene.2017.10.045.[5] S. Wang, A. Lu, and C. J. Zhong, “Hydrogen production from water electrolysis: role of catalysts,” Nano Converg., vol. 8, no. 1, 2021, doi: 10.1186/s40580-021-00254-x.[6] N. A. Burton, R. V. Padilla, A. Rose, and H. Habibullah, “Increasing the efficiency of hydrogen production from solar powered water electrolysis,” Renew. Sustain. Energy Rev., vol. 135, no. July 2020, p. 110255, 2021, doi: 10.1016/j.rser.2020.110255.[7] J. Brauns and T. Turek, “Alkaline water electrolysis powered by renewable energy: A review,” Processes, vol. 8, no. 2, 2020, doi: 10.3390/pr8020248.[8] S. Anwar, F. Khan, Y. Zhang, and A. Djire, “Recent development in electrocatalysts for hydrogen production through water electrolysis,” Int. J. Hydrogen Energy, vol. 46, no. 63, pp. 32284–32317, 2021, doi: 10.1016/j.ijhydene.2021.06.191.[9] W. Tong et al., “Electrolysis of low-grade and saline surface water,” Nat. Energy, vol. 5, no. 5, pp. 367–377, 2020, doi: 10.1038/s41560-020-0550-8.[10] T. Nguyen, Z. Abdin, T. Holm, and W. Mérida, “Grid-connected hydrogen production via large-scale water electrolysis,” Energy Convers. Manag., vol. 200, no. September, p. 112108, 2019, doi: 10.1016/j.enconman.2019.112108.[11] A. Buttler and H. Spliethoff, “Current status of water electrolysis for energy storage, grid balancing and sector coupling via power-to-gas and power-to-liquids: A review,” Renew. Sustain. Energy Rev., vol. 82, no. February, pp. 2440–2454, 2018, doi: 10.1016/j.rser.2017.09.003.[12] I. V. Pushkareva, A. S. Pushkarev, S. A. Grigoriev, P. Modisha, and D. G. Bessarabov, “Comparative study of anion exchange membranes for low-cost water electrolysis,” Int. J. Hydrogen Energy, vol. 45, no. 49, pp. 26070–26079, 2020, doi: 10.1016/j.ijhydene.2019.11.011.[13] L. Peng and Z. Wei, “Catalyst Engineering for Electrochemical Energy Conversion from Water to Water: Water Electrolysis and the Hydrogen Fuel Cell,” Engineering, vol. 6, no. 6, pp. 653–679, 2020, doi: 10.1016/j.eng.2019.07.028.[14] S. Klemenz, A. Stegmüller, S. Yoon, C. Felser, H. Tüysüz, and A. Weidenkaff, “Holistic View on Materials Development: Water Electrolysis as a Case Study,” Angew. Chemie - Int. Ed., vol. 60, no. 37, pp. 20094–20100, 2021, doi: 10.1002/anie.202105324.[15] H. K. Ju, S. Badwal, and S. Giddey, “A comprehensive review of carbon and hydrocarbon assisted water electrolysis for hydrogen production,” Appl. Energy, vol. 231, no. May, pp. 502–533, 2018, doi: 10.1016/j.apenergy.2018.09.125.[16] F. ezzahra Chakik, M. Kaddami, and M. Mikou, “Effect of operating parameters on hydrogen production by electrolysis of water,” Int. J. Hydrogen Energy, vol. 42, no. 40, pp. 25550–25557, 2017, doi: 10.1016/j.ijhydene.2017.07.015.[17] F. Gutiérrez-Martín, L. Amodio, and M. Pagano, “Hydrogen production by water electrolysis and off-grid solar PV,” Int. J. Hydrogen Energy, vol. 46, no. 57, pp. 29038–29048, 2021, doi: 10.1016/j.ijhydene.2020.09.098.